2022
DOI: 10.1155/2022/7604448
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Coupling and Driving Factors of Farmland Transfer and Labor Transfer Based on Big Data: The Case of Xinjiang, China

Abstract: Agriculture big data can use the advantages of information technology to provide data support and technical support for improving the level of farmland transfer and labor transfer. And the coupling and coordinated development of the two is an essential way to ensure the effective promotion of the rural revitalization strategy and complete the building of a moderately prosperous society in an all-round path. First, aided by the coupling coordination model and exploratory spatial data analysis, a detailed analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The study referred to previous studies [48] and the index system was built according to scientificalness, integrity, and operability to measure the development levels of FT and LM. In this study, we selected 14 indexes from three aspects to represent the degree of FT development, and 13 indexes from three aspects to represent the degree of LM development (Table 1).…”
Section: The Evaluation Index Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The study referred to previous studies [48] and the index system was built according to scientificalness, integrity, and operability to measure the development levels of FT and LM. In this study, we selected 14 indexes from three aspects to represent the degree of FT development, and 13 indexes from three aspects to represent the degree of LM development (Table 1).…”
Section: The Evaluation Index Systemmentioning
confidence: 99%
“…In the coupling theory analysis study, research scholars studied the internal mechanism of FT and LM based on different theoretical perspectives. For example, Wang et al measured the CCD of FT and LM in Xinjiang, the study found that the CCD of FT and LM in Xinjiang was at the stage of high coupling and primary coordination, and there were large differences between regions [48].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, finding new driving forces to promote rural land transfer is the main focus of future research. Existing scholars have studied various aspects of rural land transfer, including the willingness to grow nonfood crops [5], property rights systems [6], agricultural green total factor productivity [7], agricultural labor [8], agricultural socialized services [9], agricultural resource endowments [10], land tenure clarification [11], financial literacy [12], subsidy policies [13], land lease agreements [14], agriculture-related loans [15], and agricultural household start-ups [16]. In fact, the most important factor limiting farmland transfer is the shortage of disposable funds for farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Against the background of the general decrease of farmland in China, farmland in Xinjiang has increased annually (He et al, 2018;Zhang and Li, 2021) and has played an important role in maintaining China's food security strategy. The quality (Sheng et al, 2021), expansion patterns (Cai et al, 2021), water use (Hu et al, 2019), and mulch pollution (Xiong et al, 2019) of Xinjiang's farmland have attracted widespread scholarly attention, and management engineering measures such as agricultural land transfer (Wang et al, 2022;Yang and Liu, 2022) and land remediation (Liao et al, 2021) are being explored. In addition, the multifunctional value of farmland in Xinjiang has also drawn attention (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%